Studium Causa Putusan Hakim mengenai Perkara Perceraian Akibat Kekerasan dalam Rumah Tangga - Saharuddin Saharuddin; Muh. Fadli Faisal Rasyid (Jurnal Litigasi Amsir, 2022)
Domestic violence is common in Indonesian society, but victims of domestic violence in the case of a wife who is a victim even though it cannot be denied that the husband can be the victim, very rarely the case is criminally reported, the victims are more choose to end the problem with divorce. This research was conducted aiming to find out the application of Law No. 23 of 2004 concerning PKDRT is still weak in efforts to protect the rights of women and to know the basics of judges' considerations in deciding divorce cases due to domestic violence. A person's reason for filing for divorce must be legal, as permitted under Law No. 1 of 1974, Governing Law No. 9 of 1975 and Compilation of Islamic Law.